The Impact of Motivation and Job Satisfaction on Employee Performance: The Role of Engagement as a Mediator - Binter, Arnold Fredo (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
In the study, motivation and job satisfaction were shown to have an effect on employee performance, with employee engagement as mediator. Employee performance is influenced by many factors, including motivation and job satisfaction. Motivation can prompt employees to work more optimally, while job satisfaction is closely linked with productivity and commitment to the organization. Employee engagement serves as mediator in the relationship between motivation, on the one hand, and performance, on the other Data was collected via survey using a Likert scale (1-5) from 150 employees of manufacturing companies located in Jakarta and Surabaya. With the help of SmartPLS and AMOS as statistical tools, path analysis method was applied to analyze the relationship between various variables. The results show that work motivation has a significant positive impact on employee performance while job satisfaction does not have any significant effects Employees’motivation is balanced against their engagement in the job, another testament to the fact that work motivation comes from both employer and employee. Employee engagement strengthens the connection between motivation and performance, therefore it should be taken into account in the performance-enhancing strategies. In this paper we we will discuss how motivation, job satisfaction, and employee engagement can effect employee performance within enterprises.